2011
DOI: 10.1111/j.1745-7599.2011.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Finding electronic information for health policy advocacy: A guide to improving search results

Abstract: Expertise in searching electronic health policy information is a prerequisite for developing APRNs' leadership in political arenas to influence health policy and the delivery of healthcare services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Nurses prefer to seek the HRI from colleagues and experts rather than traditional sources [ 5 ]. Thus, the need for efficient searching strategies and guidelines that help nurses approach electronic synthesized research for evidence-based health-related information becomes essential [ 6 ]. Hospitals equipped with sufficient computers and Internet resources may play a great role in the future by recruiting and retaining clinical staff [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses prefer to seek the HRI from colleagues and experts rather than traditional sources [ 5 ]. Thus, the need for efficient searching strategies and guidelines that help nurses approach electronic synthesized research for evidence-based health-related information becomes essential [ 6 ]. Hospitals equipped with sufficient computers and Internet resources may play a great role in the future by recruiting and retaining clinical staff [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result implied the need to enable all health sciences students to recognize credible, reliable, and trustworthy databases and links to medical information [14]. Indeed, as Olsan et al (2011) reported, the quality of nursing care can be improved by using online health-related information [15].…”
Section: Discussionmentioning
confidence: 99%
“…State Medicaid documents from 2010 to 2012 including hospice provider announcements, informational letters, administrative rule change notices, provider bulletins, policy statements, and policy manuals were used to identify state-level implementation of ACA 2302. 17,18 The Center on Budget and Policy Priorities surveys was used to identify states in budget crisis. The Kaiser Family Foundation 50-State Medicaid Budget Survey for State provided data on 2010 to 2012 state-level Medicaid cost containment.…”
Section: Methodsmentioning
confidence: 99%
“…State Medicaid documents from 2010 to 2012 including hospice provider announcements, informational letters, administrative rule change notices, provider bulletins, policy statements, and policy manuals were used to identify state-level implementation of ACA 2302. 17,18 The Center on This study used the population of 50 states. Individual analyses were conducted for each year of the study (ie, 2010, 2011, and 2012), and states were excluded from the analysis after they implemented ACA 2302.…”
Section: Data Sources and Samplementioning
confidence: 99%